Challenges in teachers' practice of values-education in secondary schools: The case of East Gojjam zone, Ethiopia - Aschale Emiru; Amera Belayneh; Solomon Mengstie (College of education, Bahir Dar University, 2023)
The main purpose of this study was to investigate the challenges in teachers' practices of moral values-education in secondary schools. To achieve this purpose, a descriptive case study design was employed. The data was collected from students, teachers, and principals, mainly through semi-structured interviews. Based on this, interpretational and reflective analysis was made on a narrative basis. The finding suggests that there were challenges that include students' perception on the benefits of present education, abandoned religion and false narratives in the curriculum, non-supportive school leadership, lack of exemplars in relation to the value systems, lack of unity among teachers in managing student discipline, lack of authentic assessment of learning, and poor parental support. As a result, teachers were unlikely to seriously take on values-education as part of their responsibilities. It is thus implicated that the challenges need to be confronted and resolved in collaboration with moral actors. It is also advisable to take challenges as essential opportunities for innovation, criticality, and professional development rather than consider them threats. Furthermore, we suggest that other researchers conduct investigations into such sensitive issues of the century.